(untitled) (The Review of Diabetic Studies, 2025)
Background: Surgical care has become increasingly complex, requiring close interdisciplinary collaboration to ensure patient safety and optimal outcomes. Among the most critical partnerships within the surgical team is the collaboration between nursing and anesthesia professionals, whose coordinated roles span the entire perioperative continuum. Objective: This integrative review aims to synthesize current evidence on the collaborative roles of nursing and anesthesia in surgical procedures, with a specific focus on clinical interventions, patient safety practices, and surgical outcomes. Methods: An integrative review methodology was employed, drawing on peer-reviewed literature published between 2016 and 2025. Major databases including PubMed, CINAHL, and Scopus were searched. Studies addressing nursing–anesthesia roles, teamwork, perioperative care, and patient safety in surgical settings were included and thematically analyzed. Results: The findings indicate that effective nursing–anesthesia collaboration is associated with improved patient safety, reduced perioperative complications, enhanced pain management, and more efficient surgical workflows. Key enabling factors included structured communication, shared clinical decision-making, and clearly defined professional roles across surgical phases. Conclusion: Strengthening collaboration between nursing and anesthesia teams is a critical strategy for optimizing surgical outcomes and advancing patient-centered, safe surgical care.